â€œANALISIS KETERKAITAN PERINGKAT PENILAIAN KINERJA LINGKUNGAN DENGAN ECONOMIC PERFORMANCE PERUSAHAANâ€ STUDI EMPIRIS PADA PERUSAHAAN PESERTA PROPER SEKTOR AGROINDUSTRI YANG TERDAFTAR DI BEI PERIODE TAHUN 2011-2014 - EKAWATI, ANDHINI (Jurnal Akuntansi AKUNESA, 2016)
The purpose of this research is to examine the effect of environmental performance measured from PROPER (Performance Rating Program in Environmental Management) towards economic performance amongst Indonesian agriculture and basic industry (agroindustri) companies. The economic performance is measured by return on assets (ROA). Samples in this study were taken by purposive sampling technique that companies listed on Indonesian Stock Exchange and publish an annual report in 2011-2014. The statistical methods used in this study is a simple regression. Data analysis and hypothesis tests in this study using SPSS version 22. The test result for the hyphotesis in this study indicated that environmental performance is not significantly associated with economic performance. This result support the finding of Sarumpaet (2006).